Distribution of environmental and social sustainability in supply chains : analysis of green and social bullwhip effects - Harteela, Mikko (My University, 2019)
Stakeholder demands for environmentally and socially sustainable operations are at an all-time high as the repercussions of global crises, such as climate change, are becoming clearer when business is conducted “as usual”. By better understanding the distribution of sustainability in supply chains, stakeholders could apply pressure on the least sustainable tiers of the chain. Green bullwhip effect refers to the transformation of external stakeholder pressure to environmental requirements within a supply chain. Stakeholders exert pressure on the most visible company in the downstream wherefrom each tier in the chain renders the requirements content- and implementation schedule-wise more stringent for the next-in-line to create a safety buffer or in anticipation of future demands. Environmental requirements, as a result, are tightest at the upstream of the supply chain. Green bullwhip effect has been studied to some extent, whereas possible social bullwhip effect has been scarcely explored. Instead of environmental requirements, in the case of social bullwhip effect, demands for social reforms are analogously magnified throughout the supply chain. These two phenomena could shed light on sustainability patterns in supply chains. Using environmental, social and corporate governance (ESG) data from 290 European companies involved in manufacturing supply chains, analysis of variance was applied to test for statistically significant differences between the group means, groups referring to different supply chain positions and industries. Each company was given a supply chain position and an industry attribute to test the distribution of sustainability between tiers, and between industries. Results support the existence of both green and social bullwhip effect to some extent. Industry was discovered to have no effect on sustainability. Results imply that stakeholders should turn their attention towards wholesale and retail activities, as they perform the worst in comparison to other tiers in a supply chain, namely end product manufacturers and raw material suppliers/component manufacturers.
Keywords: green bullwhip effect, social bullwhip effect, sustainability, stakeholder pressure, vihreä piiskavaikutus, sosiaalinen piiskavaikutus, kestävyys, sidosryhmäpaine